Pre-selection of suppliers through an integrated fuzzy analytic hierarchy process and max-min methodology - Sen, Ceyda Guengoer; Sen, Selcuk; Bashgil, Hueseyin (TAYLOR & FRANCIS LTD, 2010)
There are a variety of analytical models for supplier selection ranging from simple weighted techniques to complex mathematical programming approaches. However, these models are specifically aimed at supporting a decision maker in a single phase, especially in the final selection phase and they have failed to consider the supplier selection process from a holistic point of view. Although the methodology presented in this paper primarily focused on the prequalification of potential suppliers, the outputs of the previous phases, namely problem definition and formulation of criteria, are used as inputs in this methodology. The methodology utilises a fuzzy analytic hierarchy process (AHP) method to determine the weights of the pre-selected decision criteria, a max-min approach to maximise and minimise the supplier performances against these weighted criteria, and a non-parametric statistical test to identify an effective supplier set. This information supports decision makers in making the final selection with effective alternative choices. Potential application of the proposed methodology is demonstrated in Audio Electronics in Turkey's electronics industry.
Keywords: supplier selection; prequalification of suppliers; fuzzy AHP; max-min approach; multi-criteria decision-making; DECISION-SUPPORT-SYSTEM; VENDOR SELECTION; AHP; CRITERIA; NEGOTIATION; MODEL; Engineering; Operations Research & Management Science